Strength and jump biomechanics of elite and recreational female youth soccer players - Chrisman, S. P.; O'Kane, J. W.; Polissar, N. L.; Tencer, A. F.; Mack, C. D.; Levy, M. R.; Schiff, M. A. (Journal of Athletic Training, 2012)
Context: Most researchers investigating soccer injuries have studied elite athletes because they have greater athletic-exposure hours than other athletes, but most youth participate at the recreational level. If risk factors for injury vary by soccer level, then recommendations generated using research with elite youth soccer players might not generalize to recreational players. Objective: To examine injury risk factors of strength and jump biomechanics by soccer level in female youth athletes and to determine whether research recommendations based on elite youth athletes could be generalized to recreational players. Design: Cross-sectional study. Setting: Seattle Youth Soccer Association. Patients or Other Participants: Female soccer players (N = 92) aged 11 to 14 years were recruited from 4 randomly selected elite (n = 50; age = 12.5 years, 95% confidence interval [95% CI]) = 12.3, 12.8 years; height = 157.8 cm, 95% CI = 155.2, 160.3 cm; mass = 49.9 kg, 95% CI = 47.3, 52.6 kg) and 4 randomly selected recreational (n = 42; age = 13.2 years, 95% CI = 13.0, 13.5 years; height = 161.1 cm, 95% CI = 159.2, 163.1 cm; mass = 50.6 kg, 95% CI = 48.3, 53.0 kg) soccer teams. Main Outcome Measure(s): Players completed a questionnaire about demographics, history of previous injury, and soccer experience. Physical therapists used dynamometry to measure hip strength (abduction, adduction, extension, flexion) and knee strength (flexion, extension) and Sportsmetrics to measure vertical jump height and jump biomechanics. We compared all measurements by soccer level using linear regression to adjust for age and mass. Results: Elite players were similar to recreational players in all measures of hip and knee strength, vertical jump height, and normalized knee separation (a valgus estimate generated using Sportsmetrics). Conclusions: Female elite youth players and recreational players had similar lower extremity strength and jump biomechanics. This suggests that recommendations generated from research with elite youth soccer players could be generalized to recreational players.